2014
DOI: 10.4103/0253-7613.129321
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant activity of N-acetyl cysteine in carbamazepine-administered rats

Abstract: Objectives:The present study evaluates the hepatoprotective activity of N-acetyl cysteine (NAC) against carbamazepine (CBZ)-induced hepatotoxicity.Materials and Methods:Rats were treated with CBZ (50 mg/kg p.o.) and CBZ supplemented with NAC 50, 100 and 200 mg/kg for 45 days, after which blood samples were collected and subjected to liver function tests. Animals were killed, liver was separated, weighed and the levels of antioxidants and liver enzymes were estimated. In addition, histopathological investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
4
10
0
Order By: Relevance
“…The slightly increased plasma ALT levels in the CBZ-treated SD rats were considered to be related to the increased liver weights. These results were consistent with the results of the studies previously reported (Maheswari et al, 2014;Iida et al, 2015). On the other hand, in the CBZ-treated SDT fatty rats, slight necrosis was noted in the centrilobular hepatocytes and the plasma levels of ALT, GU and T-BIL were increased.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The slightly increased plasma ALT levels in the CBZ-treated SD rats were considered to be related to the increased liver weights. These results were consistent with the results of the studies previously reported (Maheswari et al, 2014;Iida et al, 2015). On the other hand, in the CBZ-treated SDT fatty rats, slight necrosis was noted in the centrilobular hepatocytes and the plasma levels of ALT, GU and T-BIL were increased.…”
Section: Discussionsupporting
confidence: 93%
“…CBZ is metabolized by the hepatic CYP3A family. The main metabolic pathways of CBZ are epoxidation and hydroxylation, though conjugation reactions may also have a role (Maheswari et al, 2014;Bernus et al, 1996). 10,11-CBZ epoxide is the most important metabolic product of CBZ (Driefus and Langer, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoniazid injection with NAC treated group exhibited significant increase in albumin at 7 days, significant increase in total protein and albumin after 14 and 21 days when compared with isoniazid group. These findings were in agreement with Maheswari et al, (2014). NAC has an antioxidant and hepatoprotective efficacy against the druginduced liver injury (Saleem et al, 2018) also it has the ability to avert liver malfunction and stimulate renewal of the injured cells because it has free radical scavenging and anti-oxidant abilities (Lonare et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…In fact, the oxidation rate of every Ec (except AgEc) was significantly lower in Ringer's Lactate compared to Tris buffer, while the oxidation of LtEc was also practically negligible ( k ox = 0.04 x 10 −3 hr −1 ). This significant decrease in the oxidation rate of the Ecs in Tris buffer versus Ringer's Lactate solution may be due to the presence of two antioxidants, N ‐acetyl l ‐cysteine and sodium lactate, both of which have been shown to have antioxidant activity in vivo and in vitro, respectively …”
Section: Resultsmentioning
confidence: 99%